How Culture Authenticity Effect on Revisit Intention of Domestic Travelers? (Case Study of Bagan Ancient City) - Atar Thaung Htet (Journal of Business & Management, 2023)
This paper tries to explore the revisit intention of local travelers to Bagan's ancient city. The secondary objectives of this study are to examine the effect of cultural authenticity on the revisit intention of local travelers to ancient Bagan city. The convince sampling method was used for this study. The sample size was 368 travelers who have traveling experiences to Bagan city. A structured questionnaire was used for this study. Descriptive analysis and multiple regression analysis were used to analyze the collected data. The major findings of this study are most of the respondents are more likely to agree to make revisit intention to Bagan, objective authenticity and existential authenticity have a positive significant effect on revisit intention. According to these research findings, regional traveling organizations, and local authority bodies regulate the policies to maintain the ancient pagodas and temples and innovate the program that reflects ancient Burmese taste to attract local and foreign travelers.